The Organisation of Educational Space in the New Ukrainian School - Bilousova, Nadiia V.; Hordiienko, Tetiana V.; Demchenko, Nataliia M.; Filonenko, Olena S.; Bobro, Artur A. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The paper covers the issue of organisation of educational space of primary education in the conditions of establishment of the NUS. The purpose of the study was to determine the specific features in the organisation of educational space in foreign educational institutions and to provide recommendations for the organisation of educational space of the NUS. Background: The school begins with the organisation of new educational space as a carrier of symbolic information, which ensures additional opportunities for the cognitive, aesthetic, ethical development of the subjects of the educational process. The ideas of organising the educational space of foreign countries, with a clear division into the physical environment, curriculum, human factors, are embodied in the practice of the New Ukrainian School (NUS) to organise opportunities to meet the needs of the educational process while having its own features. Method: The authors used communicative, cognitive, transformative, systematising and control methods of teaching during the research. Results: The concept of "educational space" is described; models of organisation of educational space are presented. The paper provides the analysis of an array of works of scholars, which cover various aspects of the definition of educational space. The educational sources, which are determined by the Methodical recommendations on the organisation of the educational space of the New Ukrainian School, are analysed. Conclusion: Recommendations are given to future primary school teachers on the organisation of educational space and educational sources in classrooms of modern primary school. The general conclusions concerning the investigated problem are formulated.